Increased neurotransmitter release during long-term potentiation at mossy fibre–granule cell synapses in rat cerebellum - Sola, Elisabetta (Blackwell Science Inc, 2004)
During long-term potentiation (LTP) at mossy fibre–granule cell synapses in rat cerebellum synaptic transmission and granule cell intrinsic excitability are enhanced. Although it is clear that changes in granule cell excitability are mediated postsynaptically, there is as yet no direct evidence for the site and mechanism of changes in transmission. To approach this problem, evoked postsynaptic currents (EPSCs) and miniature synaptic currents (mEPSCs) were recorded by patch-clamp in cerebellar slices obtained from P17–P23 rats. LTP was induced by theta-burst stimulation paired with depolarization. During LTP, the EPSCs showed a significant decrease in the coefficient of variation (CV; 28.9 ± 5.2%, n = 8; P < 0.002), the number of failures (87.1 ± 41.9%, n = 8; P < 0.04), and the paired-pulse ratio (PPR; 25.5 ± 4.1%n = 5; P < 0.02). Similar changes were observed by increasing neurotransmitter release (extracellular solutions with high Ca(2+)/Mg(2+) ratio), whereas increases in CV, numbers of failures and PPR occurred when release was decreased (extracellular solutions with low Ca(2+)/Mg(2+) ratio; 10 μm Cl-adenosine). No changes followed modifications of postsynaptic holding potentials, while CV and failures were reduced when the number of active synapses was increased. LTP was prevented by use of solutions with high Ca(2+)/Mg(2+) ratio. Moreover, LTP and the associated CV decrease were observed in the spillover-mediated component of AMPA EPSCs and in NMDA EPSCs. During LTP, mEPSCs did not change in amplitude or variability but significantly increased in frequency (47.6 ± 16%, n = 4; P < 0.03). By binomial analysis changes in EPSCs were shown to be due to increased release probability (from 0.6 ± 0.08 to 0.73 ± 0.06, n = 7; P < 0.02) with a constant number of three to four releasing sites. These observations provide evidence for increased neurotransmitter release during LTP at mossy fibre–granule cell synapses.